Local Tax Implementation and Collection Effectiveness on Regional Revenue in East Manggarai - Waldoanus Jo; Aloisius Hama (CV Edujavare Publishing, 2026)
In the context of a people-centered economy, the agrarian sector plays a strategic role in contributing to state revenue through the self-assessment system, which gives full trust to taxpayers to calculate and report their obligations. This study examined the effect of local tax implementation and tax collection effectiveness on Regional Original Revenue in East Manggarai Regency. A quantitative approach with multiple linear regression analysis was applied to evaluate the relationship between variables. Data were obtained from financial reports and questionnaires distributed to tax officers. The results showed that local tax implementation had a positive and significant effect on regional revenue. Tax collection effectiveness also contributed significantly to increasing revenue realization. Simultaneously, both variables strengthened regional fiscal capacity, with a coefficient of determination of 64.2 percent. These findings indicated that improving administrative systems and optimizing tax collection performance played an important role in increasing regional financial independence. The study also suggested that strengthening digital taxation systems and improving taxpayer compliance could increase revenue sustainability in the future.